Agricultural transformation and market innovation: Theory, concepts, and definitions - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
Historically, agriculture was seen as a contribution that helped induce industrial growth and structural transformation of the economy. The structural transformation where the share of agriculture in gross domestic product (GDP) and employment declines as per capita income rises is well documented. Classical theorists, led by Lewis (1954), viewed economic development as a growth process of relocating factors of production from an agricultural sector characterized by low productivity and the use of traditional technology to a modern industrial sector with higher productivity. Economic transformation is triggered when agriculture realizes enough surplus in the form of food and commodities and product and factor markets begin to integrate across space, and workers begin to move out of agriculture to meet the demands of a growing industrial sector.